2017
DOI: 10.1186/s13018-017-0626-8
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of femoral shaft morphology in the sagittal plane in Chinese patients with osteoarthritis—a radiographic analysis

Abstract: BackgroundThe purpose of this study was to analyze femoral shaft sagittal parameters in Chinese osteoarthritis (OA) patients undergoing total knee arthroplasty (TKA) and identify whether the parameters in the coronal plane could be predictors of those in the sagittal plane.MethodsStandard long-standing anteroposterior and femoral lateral radiographs of 50 lower limbs in 50 Chinese OA patients were included. Sagittal femoral bowing angle (sFBA), angle between femoral distal anterior cortex axis and sagittal mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…Tang et al [ 28 ] recommend that the patients with obvious femoral bowing at the distal femur as seen on the preoperative long film should be used with caution when performing intramedullary guide in TKA. Similar results were found by Bao et al [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…Tang et al [ 28 ] recommend that the patients with obvious femoral bowing at the distal femur as seen on the preoperative long film should be used with caution when performing intramedullary guide in TKA. Similar results were found by Bao et al [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…Tang et al [29] recommend that the patients with obvious femoral bowing at the distal femur as seen on the preoperative long lm should be used with caution when performing intramedullary guide in TKA. Similar results were found by Bao et al [19].…”
Section: Discussionsupporting
confidence: 92%
“…The angle between the midlines drawn in the proximal and distal quarter segments was de ned as cFBA(coronal femoral bowing angle)(Fig. 1 A) [18,19,20,21]. Lateral angulation of >5°in the coronal plane was de ned as lateral FSB, also be called cFSB(coronal femoral shaft bowing).…”
Section: Radiological Evaluationmentioning
confidence: 99%
“…Sixth, we only analyzed coronal bowing. However, the results from a previous study on femoral bowing indicated a poor correlation between the parameters in the coronal and sagittal planes [31]. Moreover, in other studies on bowing [19,23,24] or reporting on the category of the alignment after TKA [20][21][22] in the coronal plane, only the parameters measured on films of the coronal plane were used.…”
Section: Oh Et Al Knee Surgery and Related Researchmentioning
confidence: 99%